2015
DOI: 10.1128/genomea.00402-15
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Halomonas sp. Strain KO116, an Ionic Liquid-Tolerant Marine Bacterium Isolated from a Lignin-Enriched Seawater Microcosm

Abstract: Halomonas sp. strain KO116 was isolated from Nile Delta Mediterranean Sea surface water enriched with insoluble organosolv lignin. It was further screened for growth on alkali lignin minimal salts medium agar. The strain tolerates the ionic liquid 1-ethyl-3-methylimidazolium acetate. Its complete genome sequence is presented in this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Halomonas spp. (Halomonadaceae) are also of interest, since they represent one of the most abundant bacterial genera within the A. vulgare microbiome [ 42 , 51 , 52 ].Their genomes possess several genes encoding LMEs, and they are known to contribute to lignin degradation [ 104 ]. Accordingly, they were identified as major contributors of LMEs in isopods from laboratory lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Halomonas spp. (Halomonadaceae) are also of interest, since they represent one of the most abundant bacterial genera within the A. vulgare microbiome [ 42 , 51 , 52 ].Their genomes possess several genes encoding LMEs, and they are known to contribute to lignin degradation [ 104 ]. Accordingly, they were identified as major contributors of LMEs in isopods from laboratory lineages.…”
Section: Discussionmentioning
confidence: 99%
“…ILs, however, can be extremely toxic to microbes and enzymes, and IL removal comes at a great expense. Halotolerant microbes or their enzymes have shown great potential to withstand IL concentrations far greater than typical lab strains, and are a potential resource for engineering IL-tolerance in biofuel-producing lab strains (Pottkämper et al, 2009 ; Gunny et al, 2014 ; Portillo and Saadeddin, 2014 ; O'Dell et al, 2015 ). Here we found that Pond A23 had a ten-fold increase in dissolved organic material over that found in Pond 2C (Table 1 ), with a corresponding abundance of CAZy AA genes primarily in the Proteobacteria and Bacteroidetes, as well as genes for low-pI AA proteins in the Euryarchaeota.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the genome analysis explains the ability of KO116 to inhabit insoluble organosolvent lignin and also its tolerance towards ionic solvents. 46 .…”
Section: Whole Genome Sequence Studies Of Lignocellulose Degrading Bamentioning
confidence: 99%